User-Informed Medical Device Development: A Case Study for Pediatric Malnutrition Assessment - Kristi Thaete MS; Kasey Rowzer MS; Karen Stephens MS; Susan M. Abdel-Rahman PharmD (SAGE Publishing, 2019)
Background . Mid-upper arm circumference (MUAC) has been extensively used to classify pediatric malnutrition. Recently, MUAC z score was recommended; however, the logistics of implementation were not addressed. This study examines the usability of a device that provides MUAC and corresponding z score range in a single device. Methods. This was a single-center study of nutrition services providers. The device was applied to children aged 2 months to 18 years admitted as inpatients or seen as outpatients. Surveys incorporated benchmarking questions, assessed the ease with which respondents could perform 6 critical tasks, and provided an open-ended question to elicit feedback. Users were surveyed monthly until saturation was reached. Survey data were analyzed in aggregate and cross-tabulated by the respondents' experience with the device. Thematic analysis of the open-ended responses followed a structured approach. Results. Sixty device users responded to the survey 280 times. Respondents were female (100%) with a mean age of 45.2 ± 13.2 years and 9.6 ± 8.0 years in practice. Increasing device use was accompanied by significantly shortened measuring times ( P < .001) and shifts in ease of performance for 5 of 6 critical tasks ( P < .05). Open-ended response themes related largely to design and materials. These were used to iteratively refine the device. Conclusions . The active engagement of end users in the real-world testing of our nutritional assessment device allowed us to refine the innovation with special attention paid to the needs of dietitians. The result is a device the majority of dietitians found easy to use, efficient, convenient, and preferable to alternative measurement options.